\(Balanites vietnamica\) (Zygophyllaceae), a new species from Vietnam - Nguyen, Tran Quoc Trung; Nguyen, Thanh Trung; Van Tiep Tran; Luu, Hong Truong (Academia Journal of Biology, 2023)
Balanites vietnamica is described as a new species from Nui Chua National Park in Ninh Thuan province, Vietnam. It is morphologically close to and has been misidentified as B. roxburghii but actually differs in many vegetative and reproductive characteristics. The new taxon is found narrowly endemic in the semi-arid Phan Rang region and its distribution area has been much reduced. The new taxon is described, illustrated with field photographs of detailed botanical characteristics and compared to related species. This rare taxon is assessed as CR following the IUCN Redlist Categories.